(untitled) (Brazilian Geographical Journal, 2011)
The cluster of on-board system is a key part of Toulouse industrial activity. This cluster links several kinds of firms from different sectors and academic laboratories, in the field of engineering, aerospace, electronics systems and software. In this presentation, we will argue that this technological cluster is partly an unexpected result of loosely connected local and national policies and industrial initiatives between 1900 and 1980. The recent “pôle de compétitivité Aerospace Valley” policy was more a result of this cluster than a cause. But from an analysis of the projects financed through the policy, we can make the hypothesis that this policy will reinforce the integration of the cluster without modifying significantly its structure.